1986
DOI: 10.1063/1.336897
|View full text |Cite
|
Sign up to set email alerts
|

Annealing of ion-implanted resistors reduces the 1/ f  noise

Abstract: The conductivity fluctuations in 1-MeV, boron-implanted layers in silicon have been investigated at room temperature with the anneal temperature as a parameter. The 1/ f  noise parameter α has been calculated from conductance, Hall voltage, and noise experiments. Annealing of the implants causes, in addition to an increase in the number of electrically active impurities, a decrease in the 1/ f  noise parameter α by a factor of at least 50. The α value is proportional to eΔE/kTan, with an annealing activation e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(27 citation statements)
references
References 16 publications
3
23
0
1
Order By: Relevance
“…On the other hand, the pure mobility fluctuation theory [14]- [16] uses an empirical relationship where the relative noise is inversely proportional to the number of carriers and proportional to a parameter [14]- [16]. Our experimental result can be explained successfully by using this approach and the extracted values are summarized in Table I which are reasonable [7], [15].…”
Section: Resultssupporting
confidence: 53%
“…On the other hand, the pure mobility fluctuation theory [14]- [16] uses an empirical relationship where the relative noise is inversely proportional to the number of carriers and proportional to a parameter [14]- [16]. Our experimental result can be explained successfully by using this approach and the extracted values are summarized in Table I which are reasonable [7], [15].…”
Section: Resultssupporting
confidence: 53%
“…Mechanical damage or implantation damage of the crystal lattice results in increasing a G ; by orders of magnitude, whereas the mobility only decreases by about 10% [8].…”
Section: Magnitude Of the Noisementioning
confidence: 97%
“…After the lattice damage had been restored by annealing at 900 1C, a exp was down to 10 À6 [8]. Fig.…”
mentioning
confidence: 99%
“…N depends on the piezoresistor volume and implant dose. Vandamme et al 11,12 showed that ␣ decreases for longer, higher temperature anneals which increase the crystal quality. The anneal diffusion length, ͱDt, where D is the temperature-dependent, dopant diffusion coefficient and t is the anneal time, is a measure of anneal effectiveness and presumably, crystal quality.…”
mentioning
confidence: 98%